Kineiies of electrocrystailisation of calonel in chloride solutions under Potentionstatic conditions - MUNASIRI, BHARDRA (Faculty of Science, University of Colombo, 1973)
A summary of the kinet ics of chemical and electro-chemical reactions are discussed. lhe next Chapter on Discussion and Interpretation of results allows our method of analysis of the i/t transients. elcccroer; stallisation transient is estimated froiu the observed transient. Different models i.ere examined and a c^est fitting rjodcl is derived for the i/1 variation in this taaAsient. The importance of epecific adsorption of chloride ions in electrocrystallisation is t&oiei from a calculation of char.-jo*transfer resistance. Our present studies on the anodic electrocrystallisation of calomel on mercury show that the Devanuthan aaacxni saouex iu ccrreci. The experimental technique used in the measurement of the i/t transient is detailed in the next Chapter* Results arc obtained a modified electrode for txj transients for five different concentrations of HC1 and I iC10/, namely 0.4u SCI, l.Oia IIC1, 0.1/» HC1 + 4 0.9’1 IIC10, , and x.tl4 HU10, . 4 4 In the fourth Chapter, the techniques available for stud/iny. the kinetics of fast reactions are shown in detail. The u>asic equation for the current due to electrochemical reactions are ^iven. -he work done by various schools of research in this field, is summarised in the fifth Chapter. The present state of knowledge of the electrocr/s tallisation of calomel is discussed here. In the next Chapter, the concepts of electrocrystailisation and factors that govern nucleation and growth are sum-harised. An intixxluction to the types of anodic electrocrysta— llisation reactions are then . dven. The theories that have Lcen developed for the stud; of electrocheaical reactions are discussed.